Interleukin-4 contributes to the shift of balance of IgG subclasses toward IgG4 in IgG4-related disease. (October 2018) - Akiyama, Mitsuhiro; Yasuoka, Hidekata; Yoshimoto, Keiko; Takeuchi, Tsutomu
Highlights: Interleukin-4, but not interleukin-21 enhances IgG4 production in IgG4-related disease. Interleukin-4 induces IgG4 production only in IgG4-related disease, but not in healthy controls. Our findings can help understanding the mechanism of IgG4 class switching in IgG4-related disease. Abstract: IgG4-related disease (IgG4-RD) is a systemic disorder characterized by elevated serum IgG4 level, which is mediated by T follicular helper 2 (Tfh2) cell. However, the cytokines responsible for enhancing IgG4 production remain unclear in IgG4-RD. The aim of this study was to identify responsible Tfh2-related cytokines (interleukin (IL)-4 and IL-21) for enhancing IgG4 production in IgG4-RD. Peripheral blood mononuclear cells obtained from consecutive patients with active, untreated IgG4-RD and healthy controls were examined. The production of both IgG and IgG4 were significantly increased by stimulation with IL-4 alone as well as IL-21 alone compared to background stimulation with anti-CD40 antibody in IgG4-RD. On the other hand, the IgG4/IgG ratio was statistically higher by stimulation with IL-4 alone compared to the other Tfh2-related cytokines including IL-21 in IgG4-RD. IgG4 production was not increased by stimulation with IL-4 in healthy controls. These results suggest that IL-4 can contribute to the shift of balance of IgG subclasses toward IgG4 compared to the other Tfh2-related cytokines in IgG4-RD.